PROBLEMATIKA REMAJA DALAM NOVEL LâÃTÃ OÃ JE SUIS NÃ KARYA FLORENCE HINCKEL - , FITRIANA PRATIWI; , Wulan Tri Astuti, SS., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is about the problems that are experienced by the main character and the cause of those problems. The research object is a teen novel titled LâÃ©tÃ© oÃ¹ Je suis NÃ© by Florence Hinckle. The novel is about a teenage boy named LÃ©o who faces many issues when he starts falling for XaviÃ¨re. Before analyzing the problems of the main character, the analysis of intrinsic elements such as theme, plot, character and characterization, setting, and point of view are first analyzed using structural theory. The problems experienced by the main character are then analyzed using Sigmund Freud's psychoanalysis theory. Based on the analysis, it can be concluded that the major issues that are experienced by Leo are related to his relationship with XaviÃ¨re. The cause of these problems is the active process of an unconscious mind. Thoughts and memories about his past always appear and affect all of his actions. These unconscious processes are the cause of many of Leo's problems.